Anti-Nociceptive Efficacy of Tramadol Following Surgical Removal of Impacted Mandibular Third Molar - Tahani A Al-Sandook; Bara S Minawah; Ataalla F Rijab (University of Mosul, College of Dentistry, 2013)
Aims of the Study: To evaluate the efficacy of analgesia mediated by preoperative 100 mg IM Tramadol to the post operative Tramadol and placebo after the surgical removal of mandibular wisdom tooth. Materials and Methods: Surgical removal of mandibular third molar was performed in three groups of individuals, total of thirty patients were anticipated in this study. All medically fit, average of age 24 + 2.2; each group consisted of ten patients. Group 1: Preoperative 100 mg Tramadol IM injection 30 minutes prior surgical operation; Group 2: Post operative 100 mg Tramadol IM injection; Group 3: Placebo or control group where distilled water IM injection was applied. All patients received post operatively Augmentin capsules 675 mg tid, and supplementary Paracetamol 500 mg tablet as required. Analgesia was assessed by Visual Analog Scale (VAS) and Verbal Pain Scale (VPS), patient satisfaction (PS), duration of post operative analgesia and total number of analgesic tablet were record-ed between groups. Results: Analgesia mediated by Tramadol was superior in its efficacy compared to control group in both pre and post operative Tramadol groups, according to VAS and VPS assessment (p= 0.001). There was no significant difference between the preoperative and post operative analgesia according to VAS and VPS; whereas there was a significant difference in PS, and duration of analgesia mediated by the preoperative injection in comparison to the post operative and control groups. Conclusion: Preoperative Tramadol analgesia was superior to post operative analgesia in PS and prolonged duration of analgesia that explain its antinociceptive effect in controlling post surgical pain.